Evidence about the use of glucocorticoids as therapy for sepsis: an integrative literature review (Research, Society and Development, 2022)
Introduction: sepsis is a systemic inflammatory disease associated with an infection with severe manifestations that occurs throughout the body. However, this infection does not necessarily have to be everywhere in the body, it can be restricted to just one place, but cause an inflammatory response throughout the body to try to control the cause of the infection. Objective: to demonstrate the current evidence on the use of corticosteroids in the treatment of sepsis in patients hospitalized in intensive care units (ICUs). Methodology: this is a descriptive research of the integrative literature review type. The descriptors were crossed, in English: "sepsis", "hemodynamic", "corticosteroids" in Portuguese: "sepsis", "hemodynamics", "corticosteroids" and in Spanish: "sepsis", "hemodynamic", "corticosteroids", in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO Information Services. Results and discussion: treatment can be done with corticosteroids in order to attenuate and modify the inflammatory response, in addition to offering an affordable cost. However, some side effects and adequate forms of administration corroborate the fact that there are some controversies regarding the use of corticosteroids, such as hydrocortisone, for the treatment of patients with sepsis, even with satisfactory results. Final considerations: corticosteroids, especially hydrocortisone, can be used to treat patients with sepsis. According to the literature used, the results are satisfactory and costing is easy to adhere to. However, the use of these drugs, even with benefits, is still controversial, due to the side effects caused, the dosage and the form of administration. Thus, discussions on this subject exist.